Radiation Embrittlement Understanding for PLIM Activities at EC-JRC-IE - Debarberis, L.; Sevini, F.; Acosta, B.; Pirfo, S.; Bieth, M.; Weisshaeupl, H.; Törrönen, K.; Kryukov, A.; Valo, M. (Проблемы прочности, 2004)
Radiation embrittlement and aging mechanisms for NPP reactor pressure vessels and vessel internals have been studied within NPP Plant Life Management (PLIM) for evaluation, prediction, and monitoring of the critical components’ service life. The main achievements of the SAFELIFE project, integrating various networks on PLIM issues, are given. Results of neutron embrittlement of model alloys are presented, and surveillance and research data on WWER reactor pressure vessel and other steels have been analyzed. Projects for the development of destructive and non-destructive testing of irradiated materials have been outlined.